Hasil UN SMP 2018 Ditinjau dari Latar Belakang Pekerjaan Orang Tua Siswa - Safari, NFN (Indonesian Journal of Educational Assessment, 2019)
The main purpose of this study is to answer the following question. Is there any influence on the parents' work background of the 2018 SMP national exam (UN) results? The population of this study is junior high school students who are studying in 2018, while the sample is junior high school students in grade 9. The reason for selecting samples is students who are attending the National Examination in 2018. The data in this study take the form of test scores and questionnaires answered by junior high students in 34 analysis of one-way variance, the following results are obtained. Based on the national average value, the work provinces in all over Indonesia, namely 3224331 students from 37859 SMP. Based on the results of the of parents of junior high school students participating in the 2018 UN influences the 2018 National Examination results is proven. This means that there is a significant effect (P <0,000) of parents' work background on 2018 UN results for subjects: Indonesian, English, Mathematics, and Sciences, both on father's work, mother's work, or both together ( Sig. 0,000). The father's occupational background is more dominant in Indonesian and Mathematics subjects (lodging factors 0.467 and -0.218) than maternal occupational backgrounds (lodging factors are 1.261 and 0.195). The maternal occupational background is more dominant in English and Science subjects (lodging factor 0.244 and -0,054) than father's occupational background (lodging factors are 0,280 and 0,066) The conclusion is that the background of the work of parents of junior high school students has a significant influence on 2018 UN results.abstrakTujuan utama studi ini adalah menjawab pertanyaan berikut. Apakah terdapat pengaruh latar belakang pekerjaan orang tua siswa terhadap hasil ujian nasional (UN) SMP 2018? Populasi penelitian ini adalah siswa SMP yang sedang belajar pada tahun 2018, sedangkan sampelnya adalah siswa SMP kelas 9. Alasan pemilihan sampel adalah siswa yang sedang mengikuti UN tahun 2018. Data dalam penelitian ini berbentuk skor tes dan kuesioner yang dijawab siswa SMP di 34 provinsi di seluruh Indonesia, yaitu 3224331 siswa dari 37859 SMP. Berdasarkan hasil analisis varian satu jalur diperoleh hasil seperti berikut. Berdasarkan nilai rata-rata nasional, pekerjaan orang tua siswa SMP peserta UN 2018 berpengaruh terhadap hasil UN 2018 adalah terbukti. Artinya terdapat pengaruh yang signifikan (P<0,000) latar belakang pekerjaan orang tua siswa terhadap hasil UN 2018 untuk mata pelajaran: Bahasa Indonesia, Bahasa Inggris, Matematika, dan IPA, baik pada pekerjaan ayah, pekerjaan ibu, maupun keduanya secara bersama-sama (Sig. 0,000). latar belakang pekerjaan ayah lebih dominan pada mata pelajaran Bahasa Indonesia dan Matematika (loding faktornya 0,467 dan -0,218) daripada latar belakang pekerjaan ibu (loding faktornya 1,261 dan 0,195. Latar belakang pekerjaan ibu lebih dominan pada mata pelajaran Bahasa Inggris dan IPA (loding faktornya 0,244 dan -0,054) daripada latar belakang pekerjaan ayah (loding faktornya 0,280 dan 0,066). Kesimpulannya adalah bahwa latang belakang pekerjaan orang tua siswa SMP sangat berpengaruh secara signifikan terhadap hasil UN 2018.